Capital shares and income inequality: Evidence from the long run - Erik Bengtsson; Daniel Waldenström (European Historical Economics Society (EHES), 2016)
This paper investigates the relationship between the capital share in national income and personal income inequality over the long run. Using a new historical cross-country database on capital shares in 19 countries and data from the World Wealth and Income Database, we find strong long-run links between the aggregate role of capital in the economy and the size distribution of income. Over time, this dependence varies; it was strong both before the Second World War and in the early interwar era, but has grown to its highest levels in the period since 1980. The correlation is particularly strong in Anglo-Saxon and Nordic countries, in the very top of the distribution and when we only consider top capital incomes. Replacing top income shares with a broader measure of inequality (Gini coefficient), the positive relationship remains but becomes somewhat weaker.
Keywords: D30; N30; 330; Wage share; Top incomes; Inequality; Wealth; Economic history